Integration of miRNA and gene expression profiles suggest a role for miRNAs in the pathobiological processes of acute Trypanosoma cruzi infection. Issue 1 (December 2017) - Ferreira, Ludmila; Ferreira, Frederico; Laugier, Laurie; Cabantous, Sandrine; Navarro, Isabela; Silva Cândido, Darlan; Rigaud, Vagner; Real, Juliana; Pereira, Glaucia; Pereira, Isabela; Ruivo, Leonardo; Pandey, Ramendra; et al.
Abstract Chagas disease, caused by the parasiteTrypanosoma cruzi, is endemic in Latin America. Its acute phase is associated with high parasitism, myocarditis and profound myocardial gene expression changes. A chronic phase ensues where 30% develop severe heart lesions. Mouse models ofT. cruzi infection have been used to study heart damage in Chagas disease. The aim of this study was to provide an interactome between miRNAs and their targetome in Chagas heart disease by integrating gene and microRNA expression profiling data from hearts ofT. cruzi infected mice. Gene expression profiling revealed enrichment in biological processes and pathways associated with immune response and metabolism. Pathways, functional and upstream regulator analysis of the intersections between predicted targets of differentially expressed microRNAs and differentially expressed mRNAs revealed enrichment in biological processes and pathways such as IFNγ, TNFα, NF-kB signaling signatures, CTL-mediated apoptosis, mitochondrial dysfunction, and Nrf2-modulated antioxidative responses. We also observed enrichment in other key heart disease-related processes like myocarditis, fibrosis, hypertrophy and arrhythmia. Our correlation study suggests that miRNAs may be implicated in the pathophysiological processes taking place the hearts of acutelyT. cruzi- infected mice.